The Maledu and Baleni cases impact on customary communities vulnerability to expropriation - Massyn, Julie-Hannah (Department of Private Law, 2023)
In 2018, two disputes between customary communities and entities seeking to exploit mineral resources came before the courts - Maledu v Itereleng Bakgatla Mineral Resources (Pty) Limited (“Maledu”) and Baleni v Minister of Mineral Resources (“Baleni”). In both cases, the courts found in favour of the communities that resided on the proposed mining sites and whose rights in land are secured by the Interim Protection of Informal Land Rights Act (“IPILRA”). At face value, these cases bolstered the position of communities' rights over mineral-rich land. However, the attempt to empower communities may have rendered them more vulnerable to the expropriation of their land. Given the Maledu and Baleni decisions, this research considers the position of customary communities whose land is subject to a mining or prospecting right, or where an application for mining or prospecting rights looms. Specifically, this research considers these kinds of communities' vulnerability to expropriation for the purposes of mining in light of these judgments. The research considers the consent requirement formulated in the Baleni judgment and argues that this requirement has made obtaining a valid mining right more difficult. It has also increased the likelihood that expropriation proceedings may be used to bypass the requirement, where community consent promises to be an insurmountable hurdle to resource extraction. The Mineral and Petroleum Resources Development Act (“MPRDA”) foresees this possibility by empowering the Minister of Mineral Resources to expropriate land for the purposes of mining. Further, the research shows, the Maledu judgment has disabled mining where a dispute resolution process under section 54 of the MPRDA is under way. The lengthy administrative processes involved in section 54 cause costly delays. However, the section 54 process could likewise be bypassed by applying section 55 of the MPRDA, which provides for expropriation. The dissertation argues that communities whose rights vis-à-vis mining companies are secured under the IPILRA remain vulnerable. Mining operations on their land should be an opportunity for socio-economic development for such communities. In acknowledging historical disadvantage and recognising communities' right to benefit from mineral deposits on their land, communities ought to be in the best position to benefit from mining ventures. However, following the Maledu and Baleni judgments, expropriation of land emerges as an attractive alternative means of engagement with communities. The research questions whether such an approach would be in the communities' best interests. Being expropriated of their land and then resettled or displaced is unlikely to benefit a community optimally, as it will sever their opportunities to benefit from the ongoing resource extraction.